Prediction of telomere length and telomere attrition using a genetic risk score: The multi-ethnic study of atherosclerosis (MESA) - Castro-Diehl, Cecilia; Smith, Jennifer A.; Zhao, Wei; Wang, Xu; Mukherjee, Bhramar; Seeman, Teresa; Needham, Belinda L. (Frontiers in Aging, 2022)
Background: Short telomere length (TL) and telomere attrition (TA) have been associated with age-related diseases. Objective: We assessed whether a genetic risk score for short TL (GRS-TL) combining seven TL-associated genetic variants identified in a European-ancestry genome-wide association study (GWAS) was associated with TL and TA over 10 years. Methods: Relative TL (T/S ratio) was measured by the quantitative polymerase chain reaction method for a sample of white, African American, and Hispanic participants, who attended Exam 1 and/or 5 of the Multi-Ethnic Study of Atherosclerosis (MESA). Our final sample included 1227 participants for the TL analysis and 1138 for the TA analysis. Participants were 45-84 years at Exam 1. We used a linear mixed effects model and adjusted for age, sex, and population structure. Models were stratified by race/ethnicity. Results: In the TL analysis, higher GRS-TL significantly predicted shorter TL (estimates= -0.18 [S.E.=0.08], P=0.02 for white; -0.18 [0.07], P<0.01 for African American; and -0.13 [0.05], P=0.02 for Hispanic) in fully adjusted models. In the TA analysis, no association between GRS-TL and TA over 10 years was found. Conclusion: Although GRS-TL was developed in European-ancestry populations, it was significantly associated with TL (but not TA) in all three race/ethnic groups examined.